(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article is devoted to the analysis of word-formative ability of the verbs of dynamic dimensional locality withe the prefix під-. The structure of the typical word-formative paradigm of the analized formatives is established, as well as the quantitative fullness of enery structural block and word-formative meaning is determined.